Inovasi Pelayanan Publik Melalui Program Sikilap (Strategi Menuju Kapuas Sehat dengan Integrasi Layanan Primer): Strategi Menuju Kabupaten Kapuas Sehat: Penelitian - Dina Rizki; Kristyan Dwijosusilo; Kresna Adhi Prahmana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The SIKILAP (Strategy Towards Healthy Kapuas Through Primary Service Integration) program is an innovation in public services that aims to improve the quality of health services in Kapuas Regency. By using an integrated approach between sectors and the application of a digital information system, SIKILAP integrates health center services, integrated health posts, private clinics, and community cadres. This program focuses on life cycle-based promotion and prevention services, in order to meet the health needs of the community in a comprehensive and responsive manner. Initial results show an increase in efficiency in recording, expansion of service coverage to remote areas, and a decrease in stunting rates in toddlers. Challenges faced include a lack of digital infrastructure, a lack of health workers trained in using information systems, and limited operational budget. Strengthening is carried out through human resource training, the formation of an integration driving team, collaboration with the private sector and educational institutions, and regular evaluation forums. The SIKILAP program is expected to be an example of national innovation for digital and collaborative primary service integration, with the aim of encouraging equal access, improving the quality of health services, and achieving the vision of a sustainable "Healthy Kapuas Regency".